Gestão documental da Fundação Municipal de Cultura e Turismo “João Bebe Água” (FUNDACT) - Santos, Rafaela Pereira dos (2020)
It is evident the interdisciplinarity of Information Science in this research, which sought to present and discuss concepts and work practices of an informative nature based on the primary documents. A work based on the main theorists of national and international archivology, such as Bellotto and Schellenberg, brought a new point of view of documentary science under the eyes of beginning researchers who contributed a lot to the effectiveness of the theoretical basis. It brings the statement of compliance with the objectives, which was the development and proposition of the Document Management Policy for FUNDACT; the document management intervention at FUNDACT; the elaboration of the instruments that make up the Document Management Policy (PGD), namely: Document Classification Plan (PCD), Document Temporality Table (TTD), Document Management Standard (NGD) and the manual with Standard Operating Procedures (POP ); the implementation of the PGD and the instruments created, through the Document Management Action Plan for the FUNDACT Archive. It covered the basic criteria for the functioning of a public archive, with instruments for retrieving information and with the necessary measures to preserve primary documents, as is the case here. Considered a qualitative, applied, documentary and exploratory research, it was possible to explore the best options to develop what was proposed. As the archive where all this work was carried out is not yet institutionalized and, consequently, is not open to the public, the researcher's action revolved around the prospect of transforming it into an effective information unit, offering researchers the informational wealth contained in historical documents from the FUNDACT collection. The documents were the objects responsible for the construction of the research and what was generated through it, and the answers obtained with the intervention, from the initial questions, raised possibilities beyond what was ideal, but everything revolving around the archival documents and dissemination through them.